Materiality and Subject in Marxism, (Post-)Structuralism, and Material Semiotics - Beetz, Johannes; SpringerLink (Online service) (London : Palgrave Macmillan UK(Imprint), 2016)
This clear and concise book investigates the relation between materiality and the subject in Marxism, (post-)structuralism, and material semiotics. It introduces the three approaches in an accessible way and serves as an introduction to different kinds of materialism and theories of the subject. For each approach, the modalities of materiality of the respective materialism are defined and the relationship between these multiple materialities and the subject are presented as specific to the theoretical approaches discussed. Beetz argues for a non-reductionist materialism, which conceives of materiality as more than matter or matter in motion. In such a materialism the subject is seen as an effect of material conditions, relations, processes, and practices. He shows how the constitution and decentering of the subject is conceptualized in the approaches presented and highlights the role of material instances in these processes. Johannes Beetz is a doctoral researcher at the Centre for Applied Linguistics at the University of Warwick, UK. He studied sociology, philosophy, and American studies at the Johannes Gutenberg-University in Mainz, Germany. His research interests include Critical Theory & Marxism, Discourse Studies, and Post-Structuralist Theory.
1. Introduction -- 2. Prelude: The Cartesian Subject and German Idealism -- 3. The Materiality of Conditions and the Subject of Ideology -- 4. Structural Causality and Material Ideology -- 5. The Materiality of Language and the Decentered Subject -- 6. Material Semiotics and the Rhizomatic Subject -- 7. Conclusion.
Keywords: Political theory; Poststructuralism; Semiotics